Gap-filling government debt maturity choice - Frederik Eidam (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Do governments strategically choose debt maturity to fill supply gaps across maturities? Building on a new panel data set of more than 9,000 individual Eurozone government debt issues between 1999 and 2015, I find that governments increase long-term debt issues following periods of low aggregate Eurozone long-term debt issuance, and vice versa. This gap-filling behavior is more pronounced for (1) less financially constrained and (2) higher rated governments. Using the ECB's three-year LTRO in 2011-2012 as an event study, I find that core governments filled the supply gap of longer maturity debt, which resulted from peripheral governments accommodating banks' short-term debt demand for "carry trades". This gap-filling implies that governments act as macro-liquidity providers across maturities, thereby adding significant risk absorption capacity to government bond markets.
Keywords: E58; E62; G11; H63; 330; Sovereign Debt; Maturity Structure; Market Segmentation; Central Bank Liquidity Provision; Long-Term Refinancing Operations